Forced Displacement and Refugees in Sub-Saharan Africa : An Economic Inquiry - Verwimp, Philip; Maystadt, Jean-Francois (World Bank, Washington, DC, 2015)
Most reports on refugees deal with the immediate needs of displaced people. This paper seeks to go beyond the emergency phase and explore the challenges surrounding protracted refugee situations. The paper examines the refugee situation in Sub-Saharan Africa from a long-term angle, from the perspective of refugees own agency as well as from the perspective of the host community. The paper aims to shed light on the economic lives of refugees in their host communities. Starting with an overview of the situation of refugees in Sub-Saharan Africa, the paper draws on findings from the literature to debunk some entrenched beliefs about refugees. The discussion of refugee crises in Burundi, Kenya, Rwanda, Tanzania, and Uganda draws some lessons. The decision to return is discussed and it is argued that the decision depends on the socioeconomic condition in the host country versus the country of refuge, integration versus return policies in place, the individual set of skills of each refugee, and his or her subjective perception of the political climate in both countries.